2016
DOI: 10.1007/s10661-016-5749-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of continuous monitoring to assess stream nitrate flux and transformation patterns

Abstract: Delivery of nitrogen from farmed fields to the stream network is an ongoing water quality issue in central North America and other parts of the world. Although fertilization and other farming practices have been refined to produce environmental improvements, stemming loss of nitrogen, especially in the soluble nitrate form, is a problem that has seemingly defied solution. The Iowa Nutrient Reduction Strategy is a policy initiative designed to implement conservation and other farm management practices to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Instream NO x ‐N processing over a three‐year period was quantified by Jones et al . () using two continuous sensors separated by 18 km in an eastern Iowa stream. Reynolds et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Instream NO x ‐N processing over a three‐year period was quantified by Jones et al . () using two continuous sensors separated by 18 km in an eastern Iowa stream. Reynolds et al .…”
Section: Introductionmentioning
confidence: 97%
“…In the U.S., diurnal and seasonal NO x -N patterns in the Mississippi River have been quantified with continuous NO x -N sensors (Bark, 2010). Instream NO x -N processing over a three-year period was quantified by Jones et al (2017a) using two continuous sensors separated by 18 km in an eastern Iowa stream. Reynolds et al (2016) subsampled 15-min NO x -N in situ measurements to quantify uncertainties associated with conventional, laborintensive water sampling strategies, showing that manual and automated grab sampling do not capture spatial and temporal variability of NO x -N loads as accurately as continuous monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Schilling and Zhang () indicated that NO 3 ‐N is particularly susceptible to leaching and export with baseflow when crop uptake is minimal or nonexistent (Dinnes et al, ). In‐stream removal rates of nitrate may be partially responsible for the nitrate depletion in baseflow, but this process is typically more prominent in reducing stream nitrate concentrations in September and October (Jones, Kim, & Schilling, ).…”
Section: Discussionmentioning
confidence: 99%
“…These factors are dynamic and highly variable in space and time, and their action can result in heavy discharges of nitrogen into the watercourses. The impact of natural factors on nitrogen losses can be modified by anthropogenic factors, including soil use and crop rotation, the application of slurry and other fertilizers, as well as the amount and method of application [4][5][6]. The diffuse pollution of water resources by nitrogen is a problem that affects the whole world, with agriculture being the main primary source of diffuse pollution of water resources [6,7].…”
Section: Introductionmentioning
confidence: 99%